2017
DOI: 10.1155/2017/6940649
|View full text |Cite
|
Sign up to set email alerts
|

A Giant Brunneroma Causing Gastrointestinal Bleeding and Severe Anemia Requiring Transfusion and Surgery

Abstract: Brunner's gland hamartoma, also called hyperplasia, adenoma, and Brunneroma, is an extremely rare benign proliferative lesion of Brunner's glands in the duodenum. While being mostly small and asymptomatic, they can result in gastrointestinal bleeding and obstruction. We report the case of a 54-year-old man presenting with melena and severe anemia requiring blood transfusion. CT scans showed a large mass of 8 cm in diameter, presumably arising in the duodenum. Endoscopic biopsies were not conclusive. As we were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
1
5
1
Order By: Relevance
“…[ 4 , 14 ] Our case presented with BGA-related blood loss, which led to hemodynamic instability. Although some studies have reported cases with gastrointestinal bleeding as the main clinical manifestation, [ 5 6 ] our case show larger lesion size. In addition, age of the patient was older (81 years) than previously reported of 76 years old.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…[ 4 , 14 ] Our case presented with BGA-related blood loss, which led to hemodynamic instability. Although some studies have reported cases with gastrointestinal bleeding as the main clinical manifestation, [ 5 6 ] our case show larger lesion size. In addition, age of the patient was older (81 years) than previously reported of 76 years old.…”
Section: Discussioncontrasting
confidence: 61%
“…[ 3 ] When they reach giant dimensions, they may obstruct the gastric outlet or duodenum, which requires surgery or endoscopic resection. [ 4 ] Although a few case reports have previously described BGA patients with gastrointestinal bleedings, [ 5 6 ] there are no systematic reports on the clinical features and treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical symptomatic presentation of BGH is caused by gastrointestinal bleeding or obstruction, leading to abdominal pain, nausea, vomiting, melena, or anemia. Two cases developed severe anemia and required blood transfusions [ 4 , 5 ]. In some cases, when the tumor obstructed the ampulla of Vater, pancreatitis or jaundice occurred [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…As Table 1 shows, in reported cases of Brunner’s gland hamartomas larger than 5 cm, all the exophytic BGH and sessile BGH are removed surgically, while Endoscopic resection was only performed in the pedunculated BGH. In addition, surgical treatment was also chosen in the pedunculated mass in the following cases: [1] Malignancy of the mass can not be excluded; [2] some emergency complications like intussusception; [3] The mass was too large, or the stalk was too thick to be removed endoscopically. Therefore, preoperative diagnosis and endoscopic evaluation are important to proper selection of the interventional approach.…”
Section: Discussionmentioning
confidence: 99%
“…Brunner’s gland hamartoma (BGH) is a benign tumor of the duodenum arising from the Brunner’s glands [2]. Most patients are asymptomatic, but some may present with common gastrointestinal symptoms such as bleeding, nausea, vomiting, and chronic abdominal pain [3]. Brunner’s gland hamartoma can be treated either by endoscopic or surgical excision [4].…”
Section: Introductionmentioning
confidence: 99%